pH-Responsive DNA Motif: From Rational Design to Analytical Applications - Zheng, Lin Lin; Li, Jin Ze; Li, Ying Xu; Gao, Jian Bang; Dong, Jiang Xue; Gao, Zhong Feng (Frontiers in Chemistry, 2021)
pH-responsive DNA motifs have attracted substantial attention attributed to their high designability and versatility of DNA chemistry. Such DNA motifs typically exploit DNA secondary structures that exhibit pH response properties because of the presence of specific protonation sites. In this review, we briefly summarized second structure-based pH-responsive DNA motifs, including triplex DNA, i-motif, and A+-C mismatch base pair-based DNA devices. Finally, the challenges and prospects of pH-responsive DNA motifs are also discussed.